Different regulation of miR‐29a‐3p in glomeruli and tubules in an experimental model of angiotensin II‐dependent hypertension: potential role in renal fibrosis. (March 2016) - Castoldi, Giovanna; di Gioia, Cira; Giollo, Fabrizio; Carletti, Raffaella; Bombardi, Camila; Antoniotti, Marco; Roma, Francesca; Zerbini, Gianpaolo; Stella, Andrea
Summary: The aim of this study was to evaluate the role of the angiotensin II (Ang II) induced‐differential miRNA expression in renal glomerular and tubulo‐interstitial fibrosis in an experimental model of Ang II‐dependent hypertension. To clarify this issue, Sprague Dawley rats were treated with Ang II (200 ng/kg per minute, n = 15) or physiological saline ( n = 14) for 4 weeks. Systolic blood pressure and albuminuria were measured every 2 weeks. At the end of the experimental period, renal glomerular and tubulo‐interstitial fibrosis was evaluated by histomorphometric analysis, after Sirius‐Red and Masson's trichrome staining. Ang II increased systolic blood pressure ( P < 0.0001), albuminuria ( P < 0.01) and both glomerular and tubulo‐interstitial fibrosis ( P < 0.01). Using laser capture microdissection and miRNA microarray analysis this study showed that miR‐29a‐3p was down‐regulated in renal tubules and up‐regulated in glomeruli. Real‐time polymerase chain reaction (PCR) experiments confirmed in Ang II‐treated rats a down‐regulation of miR‐29a‐3p in tubules ( P < 0.01), while no significant changes were observed in glomeruli. Matrix metalloproteinase‐2 (MMP‐2) was identified as putative miR‐29a‐3p target (by TargetScan, miRanda, Tarbase software) and functionally confirmed by luciferase activity assay. These data demonstrate that the effects of Ang II on miR‐29a‐3p expression in renal tubules is different from the one exerted in the glomeruli and that miR‐29a‐3p targets MMP‐2. These results suggest that the development of renal fibrosis at glomerular and tubulo‐interstitial level depends on different molecular mechanisms.